Prevalence of periodontitis in young adults living with HIV/Aids using antiretroviral therapy - Alexandre Candido da SILVA; Élcio Magdalena GIOVANI (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT The therapeutic management, as well as the HIV virus itself, has been associated with alterations at the bone level, which may also have a relationship with the maxillomandibular alveolar processes and potential development of periodontal diseases, especially periodontitis. Objective: The objective of this study was to evaluate the periodontal health condition of young adults living with HIV/AIDS, through the measurement of the Periodontal Clinical Insertion Level (CAL) and to raise general data on the health conditions facing HIV and on the quality of life of this audience. Methods: Data were collected at a Reference Center for STI/AIDS in São Paulo - SP, Brazil. The method used was guided by previously validated indicators. In total, 31 individuals aged between 20 and 24 years, both genders and using TAAP were evaluated. For the analyses, the Excel Microsoft® software was used. Results: There was a prevalence of periodontitis in the assessed public of 45.17%. In view of the quality of life, the public was classified as "Regular" and no cases of Necrozing Periodontitis were observed, which is strongly associated with HIV infection. Conclusions: The evaluated public showed a high prevalence of periodontitis, which reinforces the importance of Dentistry in monitoring People Living with HIV/AIDS, in order to prevent the worsening of periodontal diseases.